2012
DOI: 10.1177/0093854811431934
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Miranda Warnings

Abstract: The American Bar Association, via its newly adopted policy, seeks fundamental changes in procedural justice with respect to juvenile Miranda warnings. It calls for understandable Miranda warnings to educate youth in custody regarding the relevant Constitutional protections. In surveying prosecutors and public defenders, the authors collected 293 juvenile Miranda warnings that are intended specifically for youthful offenders. Length and reading levels were analyzed and compared to an earlier survey. Nearly two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 30 publications
(55 reference statements)
1
25
0
1
Order By: Relevance
“…For example, an analysis of juvenile Miranda warnings in the USA by Rogers et al (2012) found that nearly half of the 371 juvenile warnings they analyzed were excessively long (i.e., >225 words) or had a passage written at a college reading level. Eastwood et al (2012; Study 1) also analyzed the complexity of youth waiver forms in use by Canadian police organizations and found that 80% of the forms contained at least one section that required a post-secondary reading level to comprehend, and each form contained, on average, 23 difficult words (i.e., more than a Grade 7 level of education was needed to comprehend the word).…”
mentioning
confidence: 99%
“…For example, an analysis of juvenile Miranda warnings in the USA by Rogers et al (2012) found that nearly half of the 371 juvenile warnings they analyzed were excessively long (i.e., >225 words) or had a passage written at a college reading level. Eastwood et al (2012; Study 1) also analyzed the complexity of youth waiver forms in use by Canadian police organizations and found that 80% of the forms contained at least one section that required a post-secondary reading level to comprehend, and each form contained, on average, 23 difficult words (i.e., more than a Grade 7 level of education was needed to comprehend the word).…”
mentioning
confidence: 99%
“…However, CMR-II could be compared with representative Miranda warnings from national surveys. Prototypical warnings are available for different reading levels for both general (Rogers, Blackwood, et al, 2012) and juvenile warnings . Thus, the relationship of the MRCI warning to representative Miranda warnings would represent a vitally important step in establishing ecological validity.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…As designed, the CMR-II warning is intentionally brief (86 words) and simple to understand (reading level = grade 6.8). When warnings and waivers are administered together, "typical" lengths include the range from 125 to 175 words for general as well as juvenile warnings (Rogers, Blackwood, et al, 2012). Moreover, reading levels beyond the ninth grade are very common.…”
Section: Issues Of Ecological Validity and Miranda Assessmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Les chercheurs examinant les raisons qui expliqueraient de faibles niveaux de compréhension ont suggéré qu'une des raisons principales est la nature complexe du texte juridique (Rogers, Blackwood, Fiduccia, Steadham, Drogin et Rogstad 2012;Rogers, Hazelwood, Sewell, Shuman et Blackwood 2008). Certains éléments de preuve qui appuient cette explication de complexité sont présentés dans une étude récente menée par Eastwood, Snook et Luther (2012).…”
unclassified